Pan-Cancer Analysis Reveals PRIM2 as a Potential Biomarker for Diagnosis, Prognosis, and Immunomodulatory - Xi Zhang; Yuanyu Zhang; Leheng Liu; Zheng Gong; Kecheng Zhou (International Journal of Genomics)
Conclusion: This research highlights the potential of PRIM2 as a biomarker for cancer diagnosis and prognosis, and as a target for immunomodulatory therapy, offering valuable insights for clinical applications.